ASPEK SUPERORDINAT DALAM RUANGAN POJOK AWANG SELAMAT: SUPERORDINATE ASPECT IN AWANG SELAMAT’S COLUMN - Tengku Yahya, Tengku Shahrolnizam; Haron, Rohaidah (Jurnal Pengajian Melayu (JOMAS), 2020)
The cohesion aspect in the field of discourse analysis serves to connect one idea to another in a structured manner, thereby allowing the text to link well and in a way that is easily understood by readers. Hence, the cohesion aspect is vital in newspaper writing, specifically the editors’ columns, because well-organised ideas can deliver the message to readers effectively. The superordinate is one of the elements of the cohesion aspect proposed by Halliday and Hasan (1976) which incorporates the component of vocabulary device or vocabulary cohesion. This study on superordinate aspects utilised the Awang Selamat article published in the Mingguan Malaysia newspaper dated 18th September 2016. The objectives of this study are to identify the superordinate aspect in the editor’s column and analyse the use of the superordinate in the said section. Findings showed that vocabulary cohesion aspect involving the use of superordinate existed in the texts and play an important role in forming an integrated and structured connection of meanings in data. The ability of an editor’s column writer to make full use of the superordinate aspect allowed the Awang Selamat article to be easily understood and very appealing to read. It is hoped that this study on the superordinate aspect can be a guide for language researchers to understand the cohesion aspect in-depth, especially in the development of the field of discourse in the Malay language. Key words: Discourse, cohesion, superordinate, editor’s columns, lexical.